1998
DOI: 10.1038/sj.bmt.1701225
|View full text |Cite
|
Sign up to set email alerts
|

Association of pulmonary function testing abnormalities and severe veno-occlusive disease of the liver after marrow transplantation

Abstract: Summary:We investigated an association between pulmonary function testing (PFT) before bone marrow transplantation and the development of severe veno-occlusive disease (VOD) of the liver. We previously noted that reductions in diffusing capacity of the lung for carbon monoxide (corrected for hemoglobin) (D L CO c ) were associated with mortality after transplantation, but this was not caused by respiratory failure. We performed a case-series review of prospectively collected data from 307 marrow recipients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 17 publications
2
19
0
1
Order By: Relevance
“…3,[34][35][36] Recognized pretransplant risk factors for the development of VOD include older transplant recipient age, poor performance status, female gender, donor-recipient HLA disparity, advanced malignancy, prior abdominal radiation, second myeloablative transplant, reduced pulmonary diffusion capacity (DLCO) and prior liver disease including elevated AST prior to conditioning or preexisting cirrhosis. 3,34,37,38 In the pediatric literature, younger age at transplant (o6.5 years) also appears to be a risk factor for the development of hepatic VOD. 39 The type and intensity of the transplant conditioning regimen is probably the greatest determining factor of risk for developing severe VOD.…”
Section: Risk Factors For Vodmentioning
confidence: 99%
“…3,[34][35][36] Recognized pretransplant risk factors for the development of VOD include older transplant recipient age, poor performance status, female gender, donor-recipient HLA disparity, advanced malignancy, prior abdominal radiation, second myeloablative transplant, reduced pulmonary diffusion capacity (DLCO) and prior liver disease including elevated AST prior to conditioning or preexisting cirrhosis. 3,34,37,38 In the pediatric literature, younger age at transplant (o6.5 years) also appears to be a risk factor for the development of hepatic VOD. 39 The type and intensity of the transplant conditioning regimen is probably the greatest determining factor of risk for developing severe VOD.…”
Section: Risk Factors For Vodmentioning
confidence: 99%
“…In a slightly smaller study, Schwarer et al 60 found no significant association between Table 3 Previous studies that included pretransplant pulmonary function tests pretransplant lung function and the development of 'lateonset pulmonary syndrome,' defined as the presence of signs and symptoms of a respiratory illness associated with the development of abnormal PFTs with no evidence of an infectious etiology. An interesting study assessing the relationship between lung function abnormalities and severe veno-occlusive disease (VOD) of the liver after marrow transplantation was conducted by Matute-Bello et al 61 In a prospective study of 307 patients, they found that a pretransplant DL CO o70% of normally predicted was associated with a significant risk for developing VOD (OR 2.4, 95% CI 1.0-5.4; P ¼ 0.04), with the incidence of severe hepatic VOD being 36.4% among patients with a pretransplant DL CO o65% of predicted, compared to an incidence of 11.9% among patients with a pretransplant DL CO 465% of predicted (P ¼ 0.001). Studies from our group have been mainly focused on the development of AFO after HCT, which represents the most common noninfectious pulmonary complication after HCT.…”
Section: Pretransplant Pulmonary Function Testsmentioning
confidence: 99%
“…The more frequent use of these regimens for allogeneic HSCT conditioning may explain why some (but not all) studies report a higher risk of HVOD in recipients of allogeneic as compared to autologous HSCT. [11][12][13] Nonmyeloablative regimens cause considerably less acute organ toxicity, but this benefit may be offset by higher disease relapse rates. 10,14 High-dose chemoradiotherapy rapidly depletes intracellular antioxidants and represents a significant oxidative challenge to the liver.…”
mentioning
confidence: 99%